Affective Learning Strategy in the Teaching of Islamic Religious Education - M. Khozinatul Asror; M. Baihaqi (IQRO: Journal of Islamic Education, 2026)
This article aims to describe affective learning strategy in the teaching of Islamic Religious Education (PAI) and to explain its role in shaping students’ personalities, developing their behavior, and instilling Islamic values into their daily lives. This study applies a library research method by examining and analyzing scientific articles and previous studies related to affective learning strategy, the process of attitude formation, and value-based learning models within PAI instruction. The findings show that affective learning extends beyond students’ cognitive development, reaching into the strengthening of their value systems and the guidance of their behavior toward positive attitudes through habituation, exemplary modeling, and reinforcement techniques. The results further indicate that the success of these approaches depends largely on the teacher’s role as a model, mentor, motivator, and facilitator who continuously instills ethical and Islamic values within the classroom. In addition, attitude-based learning models such as the consideration model and the Value Clarification Technique developed by Jarolimek help students understand values, consciously choose them, and apply them consistently in daily life. This article concludes that the application of affective learning strategy in Islamic education can contribute to preparing learners who combine academic achievement, good character, and Islamic manners with the ability to practice Islamic values in accordance with the goals of national education